Some fixed point theorems in (3,2)-metric spaces - Dimovski, Tomi; Dimovski, Dončo (World Scientific Pub Co Pte Ltd, 2024)
In this paper, we consider [Formula: see text]-metric spaces and prove several fixed point theorems for self-mappings on [Formula: see text]-metric spaces satisfying some conditions similar to contractions in ordinary metric spaces.